DESIGN, CONSTRUCTION AND TESTING OF A SMART STATIC AND DYNAMIC OBSTACLE WALKING STICK WITH EMF DETECTOR FOR THE BLINDS USING MCU AND CONTROLLING SOFTWARE - Sani Abdullahi Adamu,; Adamu, Abdulkarim; Anas, M. S. (FUDMA Journal of Sciences, 2021)
Smart static and dynamic obstacle walking stick with EMF detector is an upgraded smart stick designed for blind people for optimal navigation and electrical safety.  An advanced blind stick prototype that allows visually challenged people to navigate walking paths and identify electronic gadgets with ease using modern technologies is hereby developed. The blind stick is integrated with ultrasonic sensor along with an EMF detector. This prototype first uses ultrasonic sensors to sense obstacles ahead using ultrasonic waves. On sensing obstacles, the sensor directs this data to the microcontroller. The microcontroller then processes this data and examine if the obstacle is close enough. If the obstacle is not that close the circuit does nothing. If the obstacle is close the microcontroller sends a signal to sound a buzzer. One more feature is that it allows the blind to detect the presence of EMF (electromagnetic field/electromagnetic waves) in the region he/she is, if there is, the microcontroller also sends a signal to a vibration motor (i.e. the output is in form of vibration), and if otherwise, the circuit does not trigger and thus, the vibration motor does nothing. The results obtained from the measurements have shown that this project work is optimally working and indeed operative.
Keywords: Arduino Nano 328, ultrasonic sensor, EMF detector, Vibration motor, Buzzer